2007
DOI: 10.1074/jbc.m703571200
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and Mechanism of Action of EHT 1864, a Novel Small Molecule Inhibitor of Rac Family Small GTPases

Abstract: There is now considerable experimental evidence that aberrant activation of Rho family small GTPases promotes the uncontrolled proliferation, invasion, and metastatic properties of human cancer cells. Therefore, there is considerable interest in the development of small molecule inhibitors of Rho GTPase function. However, to date, most efforts have focused on inhibitors that indirectly block Rho GTPase function, by targeting either enzymes involved in post-translational processing or downstream protein kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
263
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(278 citation statements)
references
References 58 publications
6
263
2
Order By: Relevance
“…Because Paks are the effectors of Rac1 (40,41), but our results revealed that RhoA is downstream to Rac1 and mediates thrombin-induced Pak2 activation, we applied a pharmacological approach to confirm these unusual observations. EHT1864, a selective inhibitor of Rac1 (39), and Rho inhibitor I, a selective inhibitor of RhoA (42), also suppressed thrombin-induced Pak2 activity (Fig. 5I).…”
Section: Thrombin-induced Thp-1 Cell Migration Depends On Gab1 and P1mentioning
confidence: 95%
“…Because Paks are the effectors of Rac1 (40,41), but our results revealed that RhoA is downstream to Rac1 and mediates thrombin-induced Pak2 activation, we applied a pharmacological approach to confirm these unusual observations. EHT1864, a selective inhibitor of Rac1 (39), and Rho inhibitor I, a selective inhibitor of RhoA (42), also suppressed thrombin-induced Pak2 activity (Fig. 5I).…”
Section: Thrombin-induced Thp-1 Cell Migration Depends On Gab1 and P1mentioning
confidence: 95%
“…Consistent with this specific mechanism of action, the inhibitory effect of DCAI is only toward SOS-catalyzed nucleotide exchange and does not affect the intrinsic nucleotide exchange by Ras. This mode of action is in sharp contrast to that of a Rac exchange inhibitor, EHT 1864, which inhibits both intrinsic and GEF-mediated nucleotide exchange for Rac (20 DCAI exhibits cellular activity in HEK-293Tcells; it attenuates the EGF-stimulated activation of Ras and blocks the recruitment of the cRaf RBD-CRD domain to the cytoplasmic membrane. Given that DCAI binds to Ras and acts as a competitive inhibitor against association of SOS with Ras, it is expected that its potency in cellular assays is in part determined by the cellular concentrations of SOS and Ras.…”
Section: Discussionmentioning
confidence: 84%
“…44 More recently, another Rac1 inhibitor (EHT 1864) has been developed which inhibits guanine nucleotide association, thus rendering Rac1 inactive. [45][46][47] The results of this study demonstrate the important roles of Rac1 in NSCLC cell proliferation and migration and compare the effects of Rac1-specific siRNA to that of Rac1 inhibition by NSC23766. One possible mechanism contributing to these multiple roles of Rac1 may be through the Rac1-dependent regulation of NFκB transcriptional activity in NSCLC.…”
Section: Acknowledgmentsmentioning
confidence: 81%